Bank Competition and Credit Standards - Ruckes, Martin (Review of Financial Studies, 2004)
This article offers an explanation for the substantial variation of credit standards and price competition among banks over the business cycle. As the economic outlook improves, the average default probabilities of borrowers decline. This affects the profitability of screening and causes bank screening intensity to display an inverse U-shape as a function of economic prospects. Low screening activity in expansions creates intense price competition among lenders and loans are extended to lower-quality borrowers. As the economic outlook worsens, price competition diminishes, and credit standards tighten significantly. Deposit insurance may contribute to the countercyclical variation of credit standards.